Occupational Hazards Education for Nursing Staff through Web-Based Learning - Tung, Chen-Yin; Chang, Chia-Chen; Ming, Jin-Lain; Chao, Keh-Ping (International journal of environmental research and public health, 2014)
This study aims to explore the efficiency of using online education as an intervention measure to prevent occupational hazards in a clinical nursing setting. The subjects were 320 female nursing staff from two hospitals in Taiwan. The questionnaire results indicated that the subjects primarily experienced human factor occupational hazards, as well as psychological and social hazards. Specifically, 73.1% and 69.8% of the subjects suffered from poor sleep quality and low back pain, respectively. After web-based learning, the experimental group had higher post-test scores than the control group in terms of knowledge, attitudes, and practices (KAP). However, there was only a significant difference (p < 0.05) in their knowledge about the prevention of occupational hazards. It is suggested that an online discussion may enhance nursing staff’s participation in web-based learning, and further facilitate their comments on negative factors. The findings can highly promote nursing staff’s attitudes and practices toward preventing occupational hazards through web-based learning.